Development of a piping system for a flow visualization water tunnel / Muhammad Aimi Aireez Zamir - Zamir, Muhammad Aimi Aireez (2022)
To measure the velocity around, and forces or pressures upon structures, the water tunnel have been created since 1947. A water tunnel is an experimental facility used for testing the hydrodynamic behavior of submerged bodies in flowing water.[5] It is very similar to a with wind tunnel but the different is use water as the working fluid, and related phenomena is investigated, such as measuring the forces on scale models of submarines or lift and drag on hydrofoils.[5] Usually water tunnel required a large space to perform the analysis.[5] The high cost needed to construct the big one with high power of pump required to produce adequate flow in the tunnel. It is expensive to buy all the components in order to build the model of water tunnel. Thus, a small of water tunnel model with low speed of flow will construct to minimize the cost. The water tunnel also important for students that want to learn about flow visualization. Due to these problem, there is a need for builds a water tunnel to overcome this problems. In group, we should create the low cost water tunnel. So, my part is design a piping system to fabricate and develop a working prototype for a flow visualization water tunnel. The scope of the project covered the study and analysis to construct a piping system of water tunnel. Besides, pipe and pump that use for the water tunnel is available in the market and the project will be placed in UiTM. Methodology is important before make the product. In fabricate of water tunnel apparatus, methodology is important before make the product. It is should include experimental design, testing, apparatus, parameters and etc. Project methodology is a body of practices, procedures and rules used by those who work in a discipline or engage in an inquiry and a set of working methods. The expected result for this project, the water tunnel will be a beneficial things in learning laminar and turbulent behaviour. It is also will be a new valuable things in University. The cost of this water tunnel is reasonable and affordable, which is about five hundreds Ringgit Malaysia (RM). Overall, this water tunnel design and development has achieved its objective and has a capability to study the flow around small scale of fundamental structures and behavior of vortex induced vibration (VIV).